POLA ASUH ORANG TUA DALAM MENDIDIK ANAK DI JORONG RABI JONGGOR KENAGARIAN RABI JONGGOR KECAMATAN GUNUNG TULEH KABUPATEN PASAMAN BARAT - Hafiza, Riza - (STKIP PGRI Sumbar, 2014)
This Research aimed to get data or information and analyze in depth the neighbor Parenting Parent Child educate terms: 1) Parenting Parents in educating children seen from the Parent level of education, 2) Parenting Parents in educating children seen from parents experience, 3) parenting parents in educating children seen from the outpouring of time parents and 4) parenting parents in educating children seen from the Total Family. the research is a qualitative study conducted in Jorong Rabbi Jonggor town Rabbi Jonggor Gunung Tuleh West Pasaman, informants taken by purposive sampling technique housewives who have school-age children from kindergarten / early childhood, elementary, junior high, high school and college. Engineering Data analyst with data reduction, data presentation and conclusion. The results showed: 1) Parenting parents viewed from the education level of mothers who have children who are studying the average school education up to secondary school level. there is generally in Jorong Rabbi Jonggor parenting parents apply for kindergarten / early childhood is demogratis, for elementary, junior college samapai generally be authoritarian. 2) Parenting parents in educating children seen from experience, parents give different parenting for children with different ages. 3) Parenting parents in educating children seen from the outpouring of time owned parent, usually the parents give time to care for children is very low at 1 hour in a day in the evening, and 4) Parenting parents in educating children seen from number of families, the average family size of 5 people, children are still studying from kindergarten to high school, live in their own homes and are still living with the nuclear family.